The implementation of Islamic Reading Corner as an Effort to Increase Literacy of Al Quran Education Park - Sabarudin, Mohammad; Muhammad, Fikri Rizkia (LPPM STAI Darul Falah, 2025)
This article discusses Community Service (PKM) activity through Community Service Program students of STAI Darul Falah at the Al Muhajirin Qur'an Education Park (TPQ) Bongas Village, Cililin District, West Bandung Regency in the field of education. The activity focused on assisting students with literacy by providing a reading corner. Basically, the effort to optimize the alphabetic culture in Bongas Village are already existed through strengthening education in religious institutions, one of which is the Al-Muhajirin Al-Qur'an Education Park. However, one of the challenges faced is the TPQ does not yet have adequate libraries, and there are no routine programs related to literacy. This needs to be improved in order to increase the enthusiasm for learning of children or students at TPQ Al Muhajirin which is located in Bongas village. The aim of this research is to increase literacy culture among students of TPQ Al-Muhajirin, hamlet (RW) 18 Bongas Village by providing Islamic reading corner facilities. The results of this community service have an impact positive towards the character development and early literacy habits for students. Apart from that, it is expected that this program can become a sustainable activity and increasingly support early literacy learning for children or students.